Imaging and Initial Management of Loin Pain in Pregnant Women in District General Hospital - Kadi, N (Nepal Journal of Obstetrics and Gynaecology, 2014)
Loin pain in pregnancy has an incidence of one per 1500- 2500. The investigation of loin pain in pregnancy poses a difficult diagnostic as well as therapeutic dilemma. This article highlights the usual imaging modalities that are used to investigate loin pain and the initial management in pregnant women. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 65-67 DOI: http://dx.doi.org/10.3126/njog.v8i2.9776